Trehaloza kao potencijalni terapeutski agens u različitim bolestima - Stevanović, Danijela; Vučićević, Ljubica; Trajković, Vladimir (Medicinski podmladak, 2023)
Trehalose is a natural non-reducing disaccharide synthesized in some bacteria, fungi, plants and insects. Due to its favorable physical and chemical properties, trehalose can replace water and stabilize macromolecules, thus protecting cells from drying out, heating and freezing. Vertebrates do not synthesize trehalose, but the beneficial effects of trehalose have been demonstrated in many diseases due to its ability to eliminate aggregates and damaged organelles, as well as to reduce hyperinflammation and oxidative stress. Trehalose induces autophagy by nuclear translocation and activation of transcriptional factor EB (TFEB) in mTOR-independent manner, but it enhances SQSTM1/p62 expression and exibits antioxidative properties in an autophagy-independent manner. Additionally, by increasing membrane fluidity, trehalose induces apoptosis in tumor cells, through the activation of caspase 3, 6 and JNK (c-Jun N-terminal kinase) signaling pathway. Taken together, in this review we summarized previous knowledge about the therapeutic potential of trehalose in different diseases such as dry eye syndrome, neurodegenerative diseases and tumors, with special reference to its underlying molecular mechanisms.
Keywords: trehalose; oxidative stess; autophagy; therapy